(3UQGY Gdbje heTcd GdJhGab GdeOQSj dOi GdWads - (3CMQTGh, GdZGdjs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2001)
(3EPG cGf ehVhY (B"(3UQGY Gdbje heTcd GdJhGab GdOQGSj dOi GdWad(B" (3jeKd GdETcGdjI GdeQcRjI dgPG GdHMK, aEf GdJacjQ aj eXGgQ GdYdGbI GdKbGajI GdbGFeI Hjf GdCSQI hGdeOQSI bO Tqcd GdeSYi GdJaSjQj GdPj hXafGg aj ebGQHI eVGejf gPg GdETcGdjI(B. (3hgcPG aef NdGd GdJSdje HCf GdUQGY Hjf CfeGW Gdbje GdCSQhjI hGdeOQSjI gh GdPj jTcd eUOQ GdaTd GdOQGSj, PgHfG Edi CLQCI gPg GdacQI GfWdGbkG ef fehPLfG GdfXQj GdeJeKd aj UQGY Gdbje(B. (3hgh GdfehPL GdPj YedfG Ydi GdJMbb ef eUOGbjJg GdJaSjQjI HfGA Ydi GfLGR OQGSI ejOGfjI ehqSYI JMcegG eLehYI ef GdELQGAGJ hGdCOhGJ GdefgLjI GdObjbI(B. (3hgj GdOQGSI GdJj CaVJ HfG HYO JMdjd HjGfGJgG hJaSjQgG Edi GNJHGQ GdaQVjJjf GdeYJeOJjf aj gPG GdHMK hEdi eLehYI ef GdfJGFL GdJj fLedgG aj eG jdj(B: - (3jXgQ HUhQI YGeI Cf GdCWaGd GdefMOQjf ef ChSGW ShSjhKbGajI eQJaYI ge CcKQ JhGabkG OQGSjkG ef CbQGfge GdefMOQjf ef ChSGW ShSjhKbGajI efNaVI(B. - (3jaVd CWaGd GdaFGJ GdeMXhXI GdfehPL GdKbGaj GdMOjK aj Mjf Cf CWaGd GdaFGJ ZjQ GdeMXhXI jKefhf CcKQ GdfehPL GdKbGaj GdCUjd(B. - (3gfGc GfLPGH hGVM ddCWaGd fMh bje GdeOQSI JHYkG dGfJeGAGJge GdShSjhKbGajI(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Children; Enfants; Valeurs et Education; Values and Education; (3GdCWaGds; (3GdJYdje hGdbjes